Аналіз методів синтезу звуку у відеоіграх та мультимедійних додатках. Частина 1 - Штепура, С. Р. (ХНУРЕ, 2024)
Audio content in video game industry helps to create an immersive world for players by filling it with environmental sounds, music, and effects. Creating sound design in video games involves a combination of recording, editing and synthesis techniques to create audio resources. Sound synthesis seems like an attractive option for solving the problem of limited memory. Instead of storing several pre-recorded audio clips in memory, synthesis allows you to create audio variations instantly. When synthesising any sound consisting of many frequencies, we can easily mislead the listener's perception by replacing several frequencies that are close to each other with one that represents them all. Quality scaling in sound synthesis aims to optimise performance for individual sound objects.
Keywords: синтез звуку; відеогра